Assessment of Long-Term Cultivation on Soil Properties and Heavy Metal Levels in Greenhouse - Samira Elweliyed; Masauda Alshatory; Aisha Alshanoukie (African Journal of Advanced Pure and Applied Sciences, 2025)
This study was conducted to assess the effect of long-term cultivation on physicochemical characteristics such as pH, organic matter (OM), electrical conductivity (EC), cation exchange capacity (CEC), and concentration of heavy metals (HMs) Cr, Cu, Cd, Mn, Zn, Ni, Fe, and Pb in greenhouse (GH) soils compared to uncultivated soils. Soil samples were collected from depths of 0 - 10, 10 - 20, 20 – 30, 30 - 40, 40 - 50, 50 - 60 cm. The findings indicate that the physicochemical properties of soil samples have experienced minor alterations compared to uncultivated soils. These changes are attributed to long-term agricultural practices and the application of chemical fertilizers. The heavy metal contents (Ni, Cr, Mn, Cu, Cd, Pb, Fe, and Zn) in greenhouse soils demonstrate that all levels are well below the maximum permissible limits. However, there is a significant accumulation of Cu, Cd, Mn, and Zn in greenhouse soils compared to uncultivated soils. The heavy metal pollution index (HPI) for various soil depths clearly shows moderate pollution levels in the greenhouse soils (1 < P ≤ 3). Moreover, the HPI value consistently decreases as soil depth increases. The Geoaccumulation index (Igeo) indicates that the greenhouse soils are either uncontaminated or only moderately contaminated, with manganese (Mn) exhibiting an Igeo value of 0.357. Soil pH demonstrates a strong negative correlation with various soil properties and several heavy metal samples from the greenhouse. Furthermore, there is a strong positive correlation between the physicochemical characteristics and most heavy metals found in the greenhouse soils. This decisive positive correlation among the soil samples confirms that they share a common source of pollution. In contrast, the observed strong negative correlations point to diverse origins and sources of pollution loads.